Quality‐of‐life assessment in French patients with metastatic melanoma in real life. Issue 3 (22nd October 2019) - Kandel, Marguerite; Dalle, Stéphane; Bardet, Aurélie; Allayous, Clara; Mortier, Laurent; Dutriaux, Caroline; Guillot, Bernard; Leccia, Marie‐Thérèse; Dalac, Sophie; Legoupil, Delphine; Saiag, Philippe; Montaudie, Henri; et al.
Abstract : Background: Significant progress was recently observed in the treatment of metastatic melanoma (MM). With >50% of patients now reaching a second line of treatment and a significant improvement in the survival rate, an assessment of quality of life (QoL) during the whole course of the disease becomes necessary. The objective of this study was to describe the QoL of patients with MM in France, from their diagnosis of advanced disease to their death, in real life. Methods: QoL data were collected through MelBase, a prospective, French, multicentric cohort dedicated to the follow‐up of adults with MM. QoL was assessed using the EuroQoL‐5D questionnaire and the Functional Assessment of Cancer Treatment (FACT)‐Melanoma questionnaire at the time of study inclusion, every 3 months, and at the time of each treatment change until death. To assess longitudinal changes from baseline to death, mixed‐effect models for repeated‐measures analyses were used to control for baseline covariates. Results: QoL was assessed in 1435 patients who were included in the study between 2013 and 2018. The median follow‐up was 9.4 months, and 47% of patients died during follow‐up. During first‐line treatment, the model‐based, mean utility score was 0.830 (95% CI, 0.818‐0.843), the mean FACT‐General score was 77.22 (95% CI, 76.23‐78.22), and the mean FACT‐Melanoma score was 129.46 (95% CI, 128.02‐130.90). At the time of a change in treatment line, there was a decrease of −0.027 (95% CI, −0.03, −0.02) in the utility score, −1.82 (95% CI, −1.88, −1.76) in the FACT‐General score, and −2.98 (95% CI, −3.05, −2.91) in the FACT‐Melanoma score compared with first‐line treatment. Conclusions: In the MelBase cohort, the QoL among patients with MM seems to be fairly stable over the whole disease course, although a small but significant decrease at time therapy is changed is observed. Abstract : With greater than 50% of patients who have metastatic melanoma reaching a second line of treatment, an assessment of their quality of life during the whole course disease becomes crucial. In the French MelBase cohort, the quality of life for patients who have metastatic melanoma is fairly stable over time.